2014
DOI: 10.1002/anie.201406320
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a Multicomponent Lithium Lithiate from a Combined X‐Ray Diffraction, NMR Spectroscopy, and Computational Approach

Abstract: An unusual lithium lithiate [Li(diglyme)2][(diglyme)Li2(C4H3S)3], made up from three carbanions, two lithium cations, and a single donor base molecule in the anion and a single lithium cation, coordinated by two donor base molecules, is investigated in a combined study including X-ray diffraction, NMR spectroscopy and computational approaches in solution and the solid state. While the multicomponent lithiate is the only species present in the solid state, solution NMR spectroscopy and computational methods wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 75 publications
2
26
0
2
Order By: Relevance
“…The model sample used for the pulse sequence development (Fig. ) consists of CDCl 3 in polydimethylsiloxane (PDMS) as alignment medium, [3b] (see also [6b,18] for related apolar gels as alignment media). A 3 mm outer diameter dry PDMS stick, cross‐linked with 200 kGy accelerated electrons, is swollen in 0.5 ml CDCl 3 in a standard 5 mm NMR tube, where 8 mM (1.4 mg) chromium (III) acetylacetonate is added to enhance the relaxation.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The model sample used for the pulse sequence development (Fig. ) consists of CDCl 3 in polydimethylsiloxane (PDMS) as alignment medium, [3b] (see also [6b,18] for related apolar gels as alignment media). A 3 mm outer diameter dry PDMS stick, cross‐linked with 200 kGy accelerated electrons, is swollen in 0.5 ml CDCl 3 in a standard 5 mm NMR tube, where 8 mM (1.4 mg) chromium (III) acetylacetonate is added to enhance the relaxation.…”
Section: Methodsmentioning
confidence: 99%
“…Especially in the latter case, the measurement of residual quadrupolar couplings (RQCs) of Spin 1 nuclei is of particular interest, as the size of RQCs and the typical absence of further interactions in, e.g. 2 H‐spectra or 7 Li‐spectra make them unique tools [5a,6] …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Apart from the obvious requirements on solubility, the small molecule may also not tolerate the presence of the alignment medium (or vice versa) and decompose (or lead to destabilization or decomposition of the medium). However, after rigorous trials, compatible media were found for moderately unstable compounds like Pd complexes involved in homogeneous catalysis and even very reactive organolithium species …”
Section: Measurement Of Residual Dipolar Couplingsmentioning
confidence: 99%
“…However, when compared with bonds lengths in monomeric Me 2 Zn, [85] the CZn bonds are shorter by 0.133 Å than that of the Zn1-C11 bond in 6, as would be expected given the linearity of Me 2 Zn and the lower coordination number of its zinc centre (i.e., CN = 2 versus 3). Donor-acceptor complex 6 was also analyzed by a combination of 1 H, 13 C and 7 Li NMR spectroscopy in the deuterated arene solvents benzene and toluene, as well as in the aliphatic hydrocarbon cyclohexane. In its 1 H NMR spectrum in C 6 D 6 solution, the TMP methyl groups appear as two separate resonances (at 1.08 and 1.46 ppm), confirming a difference in the surrounding chemical environment for the two sets of methyl groups (note that the and protons are each also split into separate resonances).…”
Section: Capture Of the Whole Parent Amine Dmpeamentioning
confidence: 99%